Response of cassava leaf area expansion to water deficit: Cell proliferation, cell expansion and delayed development - Alves, A.A.C.; Setter, Tim L. (Oxford University Press, 2004)
Background and Aims Cassava (Manihot esculenta) is an important food crop in the tropics that has a high growth rate in optimal conditions, but also performs well in drought-prone climates. The objectives of this work were to determine the effects of water deficit and rewatering on the rate of expansion of leaves at different developmental stages and to evaluate the extent to which decreases in cell proliferation, expansion, and delay in development are responsible for reduced growth. Methods Glasshouse-grown cassava plants were subjected to 8 d of water deficit followed by rewatering. Leaves at 15 developmental stages from nearly full size to meristematic were sampled, and epidermal cell size and number were measured on leaves at four developmental stages. Key Results Leaf expansion and development were nearly halted during stress but resumed vigorously after rewatering. In advanced-stage leaves (Group 1) in which development was solely by cell expansion, expansion resumed after rewatering, but not sufficiently for cell size to equal that of controls at maturity. In Group 2 (cell proliferation), relative expansion rate and cell proliferation were delayed until rewatering, but then recovered partially, so that loss of leaf area was due to decreased cell numbers per leaf. In Group 3 (early meristematic development) final leaf area was not affected by stress, but development was delayed by 4 6 d. On a plant basis, the proportion of loss of leaf area over 26 d attributed to leaves at each developmental stage was 29, 50 and 21 % in Group 1, 2 and 3, respectively. Conclusions Although cell growth processes were sensitive to mild water deficit, they recovered to a large extent, and much of the reduction in leaf area was caused by developmental delay and a reduction in cell division in the youngest, meristematic leaves.